Osteopatia como meio terapêutico nas disfunções temporomandibulares e dores orofaciais - Ferreira, Lara Tolentino [UNESP] (2015)
Temporomandibular disorders (TMD) is now considered a major cause of orofacial pain in the world population. It is an assisted pathology in a multidisciplinary way, with osteopathy as a therapeutic alternative. The objective of this study was to investigate the influence of osteopathic maneuvers Thrust Global unspecific in OAA (occiput, atlas and axis) and specific Thrust C3, individuals with TMD and orofacial pain, through further investigation. Patients were selected through the questionnaire RDC / TMD (Research Diagnostic Criteria for Temporomandibular disorders) and sent for further examinations (cerebral spinal artery test, anteroposterior sliding test of cervical vertebra C3, VAS, algometer and CT cone beam). The questionnaire was applied by a dentist calibrated and the study was blind to the physical therapist, which held the osteopathic maneuvers. Data were obtained from four times (control, zero time, 48 h and 2 months after the maneuvers) and the results were tabulated and statistically analyzed by non-parametric analysis (Friedman and Wilcoxon tests), with 5% significance level. The results showed improvement in orofacial pain, proven by VAS (<0.001) and algometer for RT muscles (0.047), RM (0.001) and LM (0.002) which showed significant difference between all time of the study, compared to the time control . For the TE muscle (0.09) the significant difference occurred only at 60 days compared to control time and time zero. The images showed significant decrease CT cone beam of the intervertebral space above the level of the cervical spine C2-C3 (0.05) C3-C4 (0.035). The study concluded that osteopathy can be used as a therapeutic means, by significantly reduce the pain of patients with TMD and orofacial pain. The osteopathic maneuvers Thrust Global unspecific in OAA and Thrust specific C3 were effective as treatment of TMD and orofacial pain and produced decreased intervertebral spaces above the levels of the cervical spine...